“You’ll never have to listen to her talk like this? With an upward inflection? At the end of every sentence?”— Fundamental frequency of female voices & linguistic misogyny in Fox’s Family Guy - Pierre Habasque (Anglophonia)
This paper explores how fundamental frequency variations may be used to stigmatize female characters in a fiction television series. The corpus is composed of a narrative arc taken from Fox’s Family Guy (season 5, episode 5). The quantitative section of the paper compares the fundamental frequency used by stigmatized female characters to three control groups: two non-stigmatized female characters, two stigmatized male characters, and two non-stigmatized male characters. Mann-Whitney statistical tests were used to compare the different groups. Results suggest that stigmatized female characters have a higher fundamental frequency as well as a higher standard deviation than all control groups. It is argued that fundamental frequency contributes to stigmatizing these characters, and that they are stigmatized because of their gender. To support this claim, the qualitative section of the paper demonstrates, with examples taken from the corpus, how prosody, vocabulary, semantics and dialogue construction are used, like fundamental frequency, to stigmatize these female characters. Relying on linguistic features which may be perceived as feminine contributes to stigmatizing these women in a process which is referred to in this paper as linguistic misogyny.